On Recent species of Tonnacypris Diebel & Pietrzeniuk, 1975 (Crustacea, Ostracoda), with new species descriptions from Mongolia - van Der Meeren, Thijs; Khand, Yondon; Martens, Koen (Zootaxa, 2009)
The ostracod species Tonnacypris estonica (Järvekülg, 1960), T. tonnensis (Diebel & Pietrzeniuk, 1975), T. edlundi n. sp. and T. mazepovae n. sp. are here reported from Mongolia. Redescriptions of females of T. glacialis (Sars, 1890) and males of T. lutaria (Koch, 1838) are included. The revised generic diagnosis maintains the main character of the anteroventral peg on the calcified part of the inner lamella of the left valve, but this character has a significant level of morphological variability between species of this genus. This is also true for several characters of soft parts, which results in a broader concept for the genus. Different ecological strategies and reproductive modes are present. New records also change the evolutionary and zoogeographical scenario of the genus.